Electrical Resistivity Structure and Helium Isotopes around Naruko Volcano, Northeastern Japan and Its Implication for the Distribution of Crustal Magma - Koichi Asamori; Koji Umeda; Yasuo Ogawa; Teruki Oikawa (International Journal of Geophysics)
The two-dimensional electrical resistivity structure beneath Naruko volcano was determined using magnetotelluric soundings. The resulting model shows that a prominent conductor exists through the middle crust to the uppermost mantle beneath the volcano. The location of the conductor agrees closely with a seismic low-velocity zone. Low-frequency microearthquakes occur near the conductor around the Moho depth. The cutoff depth of crustal earthquakes is coincident with the upper boundary of the conductor, implying that the conductor has a temperature appreciably higher than 400∘C. Furthermore, new helium isotope data from hot springs around the volcano were obtained. The spatial distribution of the observed 3He/4He ratios reveals the extent of mantle-derived materials beneath Naruko volcano. Consequently, it is apparent that the conductor determined beneath the volcano reflects the presence of high-temperature mantle-derived materials such as magmas and/or related fluids derived from active magmatism in the northeastern Japan subduction zone.